PENGARUH KONSENTRASI PATI AREN DAN MINYAK SAWIT TERHADAP SIFAT FISIK DAN MEKANIK EDIBLE FILM - Abdul Rahim; Nur Alam Nur Alam; Haryadi Haryadi; Umar Santoso (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The general aims of the research were to develop the utilization of palm sugar starch and to identify the optimal condition for processing edible film. The specific objectives of the research were to determine the palm sugar  starch and palm oil concentrations for processing the edible film from natural palm sugar starch. Processing edible film from natural palm sugar starch was done by making palm sugar starch suspensions  with various treatment concentrations of 1.6%, 2.0%, 2.4%, and 2.8% (w/v).  Whereas the palm oil concentrations were 10%, 20%, and 30% (w/w).  Parameters observed were physical, and mechanical characteristics including thickness, water vapor transmission rate (WVTR), tensile strength, and elongation. All treatments were replicated three times.  Statistical data analysis used Software Statistical Product and Service Solution (SPSS) version 13th with One Way Anova and Univariate Analysis of Variance at 5% significant level in conjunction with Duncan’s method for mean comparisons. The research result showed that the optimum condition of  palm sugar starch concentration for edible processing film was found at 2.8% (w/v) with mechanical and physical characteristics of 0.092 mm thickness, 3.737 g m-2 h-1 WVTR, 23.877 MPa tensile strength, and 1.727% elongation. Whilst the optimum condition for the palm oil concentration was 10% (w/w) with mechanical and physical characteristics of 0.097 mm thickness, 16.623 g m-2 h-1 WVTR, 21.847 MPa tensile strength, and 1.507% elongation.